1988
DOI: 10.1111/j.1432-1033.1988.tb13777.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a liver microsomal cytochrome P‐450 isoenzyme with a high affinity and metabolic capacity for coumarin from pyrazole‐treated D2 mice

Abstract: Microsomal coumarin 7-hydroxylase activity is regulated differently from several other monooxygenase enzymes, at least in mice [Wood, A. W. and Conney, A. H. (1974) Science (Wash. DC) 612-6141. Recently we found that in D2 mice this activity is strongly and selectively induced by pyrazole [Juvonen, R. O., Kaipainen, P. K. and Lang, M. A. (1985) Eur. J . Biochem. 152,. This paper describes the purification of the pyrazoleinducible cytochrome P-450 isoenzyme. Because of the lability of the protein, a special pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 32 publications
(14 reference statements)
2
23
1
Order By: Relevance
“…As we had observed previously in the case of P450 3A, related forms, we noticed large variations in the inducibility, more particularly with rifampicin. In the cultures, we did not observe any induction with pyrazole, which has been reported to induce coumarin hydroxylase in the mouse [40]. In accordance with the in vivo induction o f baboon, we noticed that phenobarbital was also a potent inducer of the P450 2A related protein in vitro.…”
Section: Immunological Reactivity Of Anti-(p450 Fi Igg) Against Microsupporting
confidence: 68%
“…As we had observed previously in the case of P450 3A, related forms, we noticed large variations in the inducibility, more particularly with rifampicin. In the cultures, we did not observe any induction with pyrazole, which has been reported to induce coumarin hydroxylase in the mouse [40]. In accordance with the in vivo induction o f baboon, we noticed that phenobarbital was also a potent inducer of the P450 2A related protein in vitro.…”
Section: Immunological Reactivity Of Anti-(p450 Fi Igg) Against Microsupporting
confidence: 68%
“…Hepatic levels of members of the P450IIIA gene family are regulated by glucocorticoids and a wide variety offoreign compounds (32). Recent studies have also indicated that in the mouse P450IIA proteins are highly inducible by pyrazole and to a lesser degree by phenobarbital (33). It is interesting that P450IIA proteins catalyze coumarin hydroxylation (34,35) and that AFB1 also contains the coumarin structure.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretically homogeneous P450 2a-5 was prepared from pyrazole-treated DBA/2N mouse livers, and NADPH-cytochrome P450 reductase was prepared from phenobarbitone-treated rat livers, as described by Juvonen et al (1988) Kaminsky et al, 1984) were added. The reaction was started with 2 mm NADPH.…”
Section: Reconstitution Experimentsmentioning
confidence: 99%